A SEMIOTIC ANALYSIS OF SHAKESPEARE’S “O MISTRESS MINE” USING RIFFATERRE’S SEMIOTIC THEORY - Amalia, Desthia (Journal of Language and Literature, 2020)
Analyzing literature works has been widely known as a complex spectrum because the words choice and  construction in any literature works can be done in free way. However, literature is known as a free instrument for people to express their feeling. The research discussed about a song entitled "O Mistress Mine" using Riffaterre's semiotic theory. The song is chosen as signifier from Shakespeare's play Twelfth night due to it represents lead character's situation for having unrequited love and a message for them to seize the day (carpe diem). O Mistress Mine might appear as a short song in the whole play but the meaning behind the lyrics convey the love line of the leads. Shakespeare's literature works has been known as a complex literature work because of his choice of words and words construction speak wihin his era. Meanwile in this era people might find out that grasping meaning from Shakespeare's literature works  is counted as complex work. Thus, the researcher chose Rifaterre's semiotic theory that includes three ways of analyzing the poem or song lyrics, in correlation to analyze further about figurative language and lead us to understand the meaning of the song. The research used qualitative method to find out symbols from the song and also using Riffaterre's semiotic theory. Purposive sampling is also used to pick the signs that have correlation with the message from Twelfth Night. The finding revealed there are three ways to analyze named displacing meaning, distorting meaning and creating meaning. Thus, there are 5 data used displacing meaning, 3 data used distorting meaning and 2 data used creating meaning. Furthermor, this research practically and theoritically can be used for the readers and students of English literature. this research practically and theoritically can be used for the readers and students of English literature.